ANALYSIS OF A JUDGE'S DECISION ON DEFAULT AGAINST A LAND GRANT AGREEMENT FROM THE PERSPECTIVE OF A GRANT CONTRACT: Study of Judge's Decision Nomor 3/Pdt.G/2023/PN.Jth - Wulan Ramazani; Saifuddin; Shabarullah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This article aims to analyse the judge's reasoning in Decision No. 3/Pdt.G/2023/PN.Jth regarding the default of a conditional land grant agreement between the plaintiff and the defendant. This case focuses on a land grant agreement that was made orally, with the condition that the plaintiff's child be appointed as a community service worker at the Puskeswan. The approach that the author uses is normative juridical research. The results showed that the judge considered the oral agreement invalid because it did not fulfil the applicable legal requirements, including the authority of the defendant in the appointment of community service personnel, as well as a violation of the principle of grants that must be made without compensation. As a result, the plaintiff's claim was rejected because there was no evidence or fulfilment of legal requirements. This research shows the importance of fulfilling legal requirements in conditional grants to prevent default